Determinants of Group Performance of Women-led Agro-processing Self-help Groups in Kerala - Lina Joy, A. Prema and S. Krishnan (Agricultural Economics Research Review Vol. 21 (Conference Number) 2008 pp 355-362, 2008)
Factors determining the group performance of women-led self-help groups (SHGs) engaged in agroprocessing organized under Swarnajayanti Gram Swarozgar Yojna (SGSY) in Kerala have been studied following the multi-stage purposive and random sampling technique in the Thrissur district. It has been observed that socio-economic variables like age, education, market perception, economic motivation, attitude towards self-employment, management-orientation, risk-orientation, innovativeness and information-seeking behaviour influence the group performance of SHGs. The BPL women in SGSY-SHGs of the performing groups are around 30 years of age, with middle school level education. Education and age of respondents have negative correlation on group leadership. The group stability has been determined by factors like group cohesion, group leadership, team spirit, group decision-making and regularity in maintenance of records. Correlation analysis between group performance and socio-economic characters has revealed that management-orientation has a positive and significant influence on all the determinants of group performance, followed by informationseeking behaviour, knowledge about processing, market perception and economic motivation. The parameters like age of respondent, education of spouse, attitude towards self-employment and innovativeness have been found least influential on group performance. The study has indicated the need of providing training on management and technical aspects as well as provision of market infrastructure to the SHGs so that they could become competitive in the market